Artificial intelligence and Quality Education: The Need for Digital Culture in Teaching - Donatella Padua (Journal of Educational, Cultural and Psychological Studies)
INTELLIGENZA ARTIFICIALE E ISTRUZIONE DI QUALITÀ: LA NECESSITÀ DELLA CULTURA DIGITALE NELL’INSEGNAMENTO